Rancang Bangun Website Budaya Rongkong Sebagai Media Promosi Pariwisata - Richo Pratama; Vicky bin Djusmin; Nirsal (Ikatan Ahli Informatika Indonesia, 2024)
This study aims to build a website to introduce culture and tourism in Rongkong, North Luwu Regency, so that Indonesian people can get to know the culture in Rongkong. The data collection techniques used by the author are by conducting observations, interviews and literature studies. The research method used is waterfall and uses black box testing techniques. From the results of the research conducted, it can be concluded that the Rongkong Cultural Website as a Tourism Promotion Media is feasible to use because the test results can be accepted by the system and are ready to use.